Navigating ICTs for extension and advisory services - Saravanan, Raj; Sulaiman, V. Rasheed; Davis, Kristin E.; Suchiradipta, Bhattacharjee (Global Forum for Rural Advisory Services, 2018)
Improved availability of, and access to, information and communication technologies (ICTs) – especially mobile phones, computers, radio, internet, and social media – has provided many more opportunities for collection, processing, storage, retrieval, managing, and sharing of information in multiple formats. Some of these applications, such as tele-centres, web-portals, call centres, mobile apps, community radio, digital videos, audio and video conferencing, and e-learning platforms, have the potential to provide a wide range of services (information, awareness, promotional, advisory, knowledge, technology transfer, training, education, and much more) to farmers and other agricultural innovation system (AIS) actors in a timely, comprehensive, cost-effective, and interactive manner. However, the high number and rapidly changing availability of ICTs may leave extension managers confused as to which methods are available and when to use them. This note explains how to navigate the many types and gives tips on when to use them.